NEONATAL GOITER WITH AIRWAY AND OESOPHAGEAL COMPRESSION WHICH IMPROVED WITH L-THYROXINE AND A CONSERVATIVE APPROACH - Nordin, Faizura (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Congenital goitre occurs rarely in neonates and it becomes an emergency when it causes significant airway compromise in newborns transitioning from foetal to postnatal life. neonatal goitre is closely related to thyroid status and could be either a transient or permanent genetic condition. CASE Foetal ultrasound in 2nd trimester detected an anterior neck mass with increased vascularity. At 38 weeks gestation, a baby girl was delivered with a birth weight of 3.37 kg, length of 51 cm and OFC of 33 cm. She was intubated with ETT size 3.0 and ventilated in NICU. Examination showed a diffuse neck swelling measuring 3 x 3 cm. Ultrasound and CT scan showed an enlarged right thyroid lobe 3.5 x 2.7 x 4.2 cm (AP x W x CC) and a left thyroid lobe 3.1 x 2.8 x 4.3 cm (AP x W x CC) with no cystic component or calcification. Thyroid lobes extended up to the angle of the mandible and inferiorly until thoracic inlet with the airway and esophagus almost circumferentially encased and airway patency only maintained by ETT. Cord TSH 25.12 m IU/L, fT4 10.0 pmol/L, while Day 5 TSH 37.41 m IU/L, 6.47 pmol/L. ATPO, ATG & TSH receptor antibodies were negative. Her thyroglobulin level was low at 0.6 ng/ml (intact thyroid, 3.5-77.0). Her mother also reported onset of goitre following 1st trimester. She complained of tiredness and started taking Himalaya salt. Urine iodine results for patient and mother results were 322.7 ug/L and 221.3 ug/L, respectively (250 - 499, sufficient for pregnant mother). She was treated with L-thyroxine at day 5 of life at 50 mcg daily (15 mcg/kg) with serial ultrasound neck and flexible endoscopic assessment. She was successfully extubated by day 26 and discharged after 1 month. On follow-up, her goitre remained small with normal development and hearing. Due to cost constraint, genetic test was not pursued. CONCLUSION Neonatal goitre with hypothyroidism may result from maternal ingestion of antithyroid drugs or goitrogens, transplacental transfer of antithyroid antibodies, or thyroid dyshormonogenesis. Low thyroglobulin level with raised TSH and low fT4 suggest thyroglobulin synthetic defect.